The use of molecular modelling for process development of Au-Bi- Fe3O4 ores - A. Pshennikov; N. Voyloshnikova; P. Solozhenkin; N. Nehoroshev (International Mineral Processing Congress, 2014)
"Molecular modeling of clusters of major bismuth minerals, Bi2S3, was carried out whereby molecular models of minerals and reagents clusters were created. Their HOMO and LUMO energy levels were calculated and using known modelling equations, the absolute hardness ?, eV and electronegativity were calculated. The charges of separate atoms of clusters and the change of properties of the minerals were determined which allowed predictions of the flotation properties of raw ores containing rare bismuth minerals. Modeled complexes containing the clusters of minerals and various collectors were constructed, consisting of atoms and bonds within clusters of minerals. Major physical and chemical parameters were determined for the complexes created, including the total and electronic energy. Based on the energy calculations, predictions of the collector efficiency were proposed. The efficiency of collector was established for various thiolic reagents, the compounds of phosphorus (III) and mixtures of reagents. Theoretical results were checked and confirmed against laboratory ore flotation tests. A gold-bismuth-magnetite ore type was studied where gold, bismuth and iron (magnetite) are of industrial interest. The ore contains 2.8 g/t Au, 1.0 g/t Ag, 0.26% Bi, 45% Fe and 1.25% As. Sulphide mineralization can be mainly found in the form of pyrrhotite, pyrite and arsenopyrite. Bismuth can be mainly found in the form of bismuthite and native bismuth. Gold is fine. A flow sheet for Zhelezny Kryazh ore treatment was proposed. This flow sheet consists of grinding to 95-98% -74 µm, sulfide flotation with two cleaner with xanthate addition, cyanidation of flotation concentrate and flotation tailings included treatment with with CaO (6 kg, 6 hours), cyanidation (8 hours) and CIL (8+24 hours). Saleable products are gold doré, bismuth and iron concentrate."